Effect of successive ionic layer adsorption and reaction (SILAR) process on various CdSe/P3HT hybrid solar cells - Goh, Kelvin Ming Ming. (2011)
Advantages of both inorganic and organic solar cells were brought together in a hybrid solar cell. Recent developments were carried out on these devices to improve their efficiencies. However, several factors limit the performance of hybrid solar cells and one such factor is the inorganic/organic interface.